Cellular Automata and Discrete Complex Systems: 25th IFIP WG 1.5 International Workshop, AUTOMATA 2019, Guadalajara, Mexico, June 26-28, 2019, Proceedings - Castillo-Ramirez, Alonso; Oliveira, Pedro P. B. de (Lecture Notes in Computer Science, 2019)
This volume constitutes the refereed proceedings of the 25th IFIP WG 1.5 International Workshop on Cellular Automata and Discrete Complex Systems, AUTOMATA 2019, held in Guadalajara, Mexico, in June 2019.The 7 regular papers presented in this book were carefully reviewed and selected from a total of 10 submissions. The topics of the conference include deal with dynamical, topological, ergodic and algebraic aspects of CA and DCS, algorithmic and complexity issues, emergent properties, formal languages, symbolic dynamics, tilings, models of parallelism and distributed systems, timing schemes, synchronous versus asynchronous models, phenomenological descriptions, scientic modeling, and practical applications.